ANALISIS KAUSALITAS ANTARA PENERIMAAN PAJAK DENGAN TINGKAT KEGIATAN EKONOMI INDONESIA DENGAN PENDEKATAN GRANGER CAUSALITY - Abubakar Arif; R Rosiyana Dewi (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2013)
The purpose of this study is to analysis the causality between tax revenue and economy activity in Indonesia period 1990-2010. The design of this research used time series analysis model with Granger Causality Model with the step analusis are (1) determine long of lag to know how long tax revenue and economy activity influence, (2) determine causality test to proof there are causality or there are correlation one direction between tax revenue and economy activity, (3) analyze the power of correlation or influence between tax revenue and economy activity after the result of causali8ty test was reach. The analysis used in this research was time serieswith annual data,starting 1990 too 2010. Tax revenue and economy activity with proxy product domestic bruto are valuables used in this study. The result of this study are not find causality between tax revenue and economy activity in Indonesia but one direction correlation when tax revenue influence economy activity.By the regression analysis can proff that tax revenue influence significant positive to economy activity with multiplier effect less than 1.